FA’AALIYYAH ‘AMALIYYATH MUHAADHARAH AL-LUGHAH AL-‘ARABIYYAH ‘ALAA MAHARAH AL-KALAAM LIL MAJMU’AH (OCC) BI MA’HAD UMMUL QURO AL-ISLAMI BOGOR - Ainun; Lukman Taufik Akasahtia; Asriani (SHAWTUL ARAB, 2021)
This research defines the identification of the educational activities of the lecturer and to know how to speak Arabic in the Orientation Courses Club (occ), and this study is to determine the effectiveness of the aim of the speaker in improving Arabic speaking skills in the Orientation Courses Club (occ) at the Umm Al-Qura Islamic Institute, Bogor. It is hoped that teachers will pay more attention to the students' learning process, especially in participating in limited Arabic activities and Arabic speaking skills. They should have an awareness of each individual, to be motivated to participate in the activities of limited Arabic and speak Arabic frequently and should be used as assessment materials in which Arabic modernization activities can be used as a way to improve Arabic speaking skills